LAJU DEKOMPOSISI SERASAH DAUN Rhizhopora apiculata PADA BERBAGAI TINGKAT SALINITAS DI KAMPUNG NYPA DESA SEI NAGALAWAN KECAMATAN PERBAUNGAN - Dilla Ersyahdes Riski; Yunasfi Yunasfi; Hesti Wahyuningsih (Program studi Kehutanan USU, 2016)
Mangrove litter has been decomposed contributes organic matter as food source for many organism and also to give fertility in the mangrove ecosystem. The purpose of this research were to measure the decompotion rate and to know the nutrient of carbon (C), nitrogen (N) and phosphorus (P) contained in the leaf litter of R. apiculata at the various levels of salinity. This research was done at Kampung Nypa Desa Sei Nagalawan Perbaungan, North Sumatera Province from August 2015 until January 2016 with used 50 grams of leaf litter. This research for decomposition rate of R. apiculata used Olson method. Nutrient analysis of carbon was conducted using Walkey & Black method, analysis of nitrogen and phosphorus nutrients was conducted using the extraction of wet destruction. The results showed the fastest weight loss and the rate of decomposition of R. apiculata leaf litter was at 0-10 ppt. The highest of levels of carbon nutrients was in 10-20 ppt, the highest of levels nitrogen and phosphorus nutrients was at 0-10 ppt Keywords: Decomposition rate, nutrient, leaf litter, R. apiculata, salinity.